PENGARUH MARKET ORIENTATION TERHADAP COMPETITIVE ADVANTAGE DENGAN INTEGRATED MARKETING COMMUNICATION DAN CUSTOMER ENGAGEMENT SEBAGAI VARIABEL INTERVENING PADA TELKOMSEL DI SURABAYA - Andy Andy (Jurnal Strategi Pemasaran, 2016)
Smartphone users in the world keep increasing especially during 2015 in Indonesia. This increasing users will affect the number of needs in Indonesia telecommunication cellular operator, especially in Surabaya. This issue also affected higher competition, which telecomunication firm try to maintaining and increasing the number of customer.This research aims to analyze the effects of market orientation to competitive advantage with integrated marketing communication and customer engagement as intervening variable in Telkomsel at Surabaya.This research used quantitative analysis with path model method for the technical analysis and distributing questionnaires to 120 Telkomsel users in Surabaya,